Two-sided inequalities with nonmonotone sublinear operators - Kopach, M.I.; Obshta, A.F.; Shuvar, B.A. (Carpathian Mathematical Publications, 2015)
The theorems on solutions and their two-sided estimates for one class of nonlinear operator equations x=Fx with nonmonotone operators.